PSIKOLOGI PEREMPUAN DALAM AL-QUR'AN: Reinterpretasi QS. Az-Zukhruf Ayat 18 Dengan Pendekatan Historis Dan Neurosains (TAJDID: Jurnal Ilmu Ushuluddin, 2024)
Gender justice and equality have been prominent issues in recent decades. Despite Islam being a religion that upholds the values of justice and equality, in reality, Arab and Muslim-majority countries have been significant contributors to patriarchy. One factor is the misinterpretation of gender-biased Quranic verses, disregarding egalitarian Islamic principles and values, such as in the interpretation of Surah az-Zukhruf: 18. Women are often perceived as being limited to adornment and incapable of expressing their arguments in debates. This study conducts an in-depth analysis of this verse to understand the psychology of women's inclination towards adornment and their intelligence. This is a qualitative study utilizing literary sources that are then analyzed using historical and neuroscientific approaches. The analysis reveals that women's tendency to adorn themselves and have an attractive appearance is due to estrogen hormones which stimulate the brain to develop these impulses. Hormonal fluctuations in women significantly impact brain function, including increasing women's tendency to engage in social interactions and avoid conflict and debate. However, this does not necessarily indicate lower cognitive or verbal abilities in women. Both women and men are created with different brain structures, each with their own strengths. These differences exist to complement each other in living a better life.